GC−MS Study of Volatiles of Normal and Microbiologically Attacked Cork from Quercus suber L. - Rocha, Sílvia; Delgadillo, Ivonne; Ferrer Correia, A. J. (Journal of Agricultural and Food Chemistry, 1996)
The volatile compounds of cork were studied by gas chromatography and combined gas chromatography?high-resolution mass spectrometry using simultaneous distillation?extraction to prepare the samples. To assess the origin of the volatiles, three different types of samples were analyzed:? ?normal?, attacked by Armillaria mellea, and infested by molds. The study of the volatiles of these different types of corks allowed the identification of the chemical modifications which may occur in cork polymers. The cork attacked by A. mellea showed higher amounts of phenols, vanillin, benzaldehyde, benzyl alcohol, and chlorinated compounds than normal cork; this may indicate lignin degradation. The cork infested by molds contained higher levels of 3-methyl-1-butanol, 1-octen-3-ol, 1-octanol, 2-methylisoborneol, chlorinated compounds, and methyl ketones. These components resulting from microbial metabolism were also present in cork attacked by A. mellea. The use of cork attacked by A. mellea is not recommended in the manufacture of cork stoppers, since these types of cork have volatile compounds likely to cause off-flavors in wine. For the same reason it is important to reduce the likelihood of mold development during the standing period. Keywords: ?Normal? cork; Armillaria mellea; molds; volatile components; musty and moldy odors
doi: 10.1021/jf9500400doi: 10.1021/jf9500400The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Armillaria mellea; molds; musty and moldy odors; volatile components; “Normal” cork

GC−MS Study of Volatiles of Normal and Microbiologically Attacked Cork from Quercus suber L. (Journal of Agricultural and Food Chemistry, 1996)
The volatile compounds of cork were studied by gas chromatography and combined gas chromatography?high-resolution mass spectrometry using simultaneous distillation?extraction to prepare the samples. To assess the origin of the volatiles, three different types of samples were analyzed:? ?normal?, attacked by Armillaria mellea, and infested by molds. The study of the volatiles of these different types of corks allowed the identification of the chemical modifications which may occur in cork polymers. The cork attacked by A. mellea showed higher amounts of phenols, vanillin, benzaldehyde, benzyl alcohol, and chlorinated compounds than normal cork; this may indicate lignin degradation. The cork infested by molds contained higher levels of 3-methyl-1-butanol, 1-octen-3-ol, 1-octanol, 2-methylisoborneol, chlorinated compounds, and methyl ketones. These components resulting from microbial metabolism were also present in cork attacked by A. mellea. The use of cork attacked by A. mellea is not recommended in the manufacture of cork stoppers, since these types of cork have volatile compounds likely to cause off-flavors in wine. For the same reason it is important to reduce the likelihood of mold development during the standing period. Keywords: ?Normal? cork; Armillaria mellea; molds; volatile components; musty and moldy odors
doi: 10.1021/jf9500400

Improvement of the Volatile Components of Cork from Quercus suber L. by an Autoclaving Procedure (Journal of Agricultural and Food Chemistry, 1996)
The volatiles of cork slabs submitted to a novel industrial treatment, autoclaving, were compared with the volatiles of the untreated slabs to establish the usefulness of this treatment as a cleanup procedure. The condensed steams corresponding to the first and a second autoclaving process were also analyzed. The volatile compounds of cork and of autoclaved condensed steam were extracted by simultaneous distillation?extraction and analyzed by gas chromatography and combined gas chromatography?high-resolution mass spectrometry. Cork slabs treated with steam under pressure showed smaller amounts of the volatile components with musty, moldy, and related odors, such as 3-methyl-1-butanol, 1-octanol, and guaiacol and other mold metabolites. The condensed steam contained compounds corresponding to those extracted from the cork. The autoclaving process has potential for industrial use to clean the cork and to reduce volatiles of microbial origin in cork samples. Keywords: Quercus suber L.; volatiles; autoclaving process; condensed steam; musty and moldy odors
doi: 10.1021/jf950041s